2012
DOI: 10.1063/1.3686258
|View full text |Cite
|
Sign up to set email alerts
|

Benchtop energetics progress

Abstract: Abstract.We have constructed an apparatus for investigating the reactive chemical dynamics of mgscale energetic materials samples. We seek to advance the understanding of the reaction kinetics of energetic materials, and of the chemical influences on energetic materials sensitivity. We employ direct laser irradiation, and indirect laser-driven shock, techniques to initiate thin-film explosive samples contained in a high-vacuum chamber. Expansion of the reacting flow into vacuum quenches the chemistry and prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…Using a first generation apparatus [5,6] we were able to observe products of in-vacuum deflagration of PETN samples [7] shock initiated by laser-driven flyers [8]. However, we did not observe the hyperthermal final products expected from detonation-like events.…”
Section: Introductionmentioning
confidence: 78%
“…Using a first generation apparatus [5,6] we were able to observe products of in-vacuum deflagration of PETN samples [7] shock initiated by laser-driven flyers [8]. However, we did not observe the hyperthermal final products expected from detonation-like events.…”
Section: Introductionmentioning
confidence: 78%
“…Experiments by Thomas et al [32] showed that the detonation products expanding toward vacuum achieve terminal velocities in the range of 8 to 12 mm/µs. Fajardo et al [33], reported the leading-edge velocities of species through the vacuum approximately ≈ 10 mm/µs in their experiments on aluminum ablation. Lundborg [34] measured the velocity of the shock front of TNT evacuating from chambers and the velocity increased from 10 mm/µs to 20 mm/µs with decreasing pressure.…”
Section: Tablementioning
confidence: 95%
“…Trunov et al [13] measured adiabatic flame temperatures for the titanium-boron reaction of approximately 2400-3300 K. One expects, similar to the values measured experimentally at low temperatures [20], that the binary diffusivities of both, boron and titanium into titanium-diboride, are significantly smaller than the mixture thermal diffusivity, and that D 23 D 13 . Taking D 23 /D 13 = 10 as a base-line model value, and the estimate T f = 3000 K for the flame-sheet temperature, our formulas (33) and 34…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…Experiments by Thomas et al [32] showed that the detonation products expanding toward vacuum achieve terminal velocities in the range of 8 to 12 mm/µsec. Fajardo et al [33], reported the leading-edge velocities of species through the vacuum approximately ≈ 10 mm/µsec in their experiments on aluminum ablation. Lundborg [34] measured the velocity of the shock front of TNT evacuating from chambers and the velocity increased from 10 mm/µsec to 20 mm/µsec with decreasing pressure.…”
Section: Example 1: An Explosive Modeled By the Ideal Gas Eos Form Whmentioning
confidence: 95%